Role of Complement in Multiorgan Failure - Daniel Rittirsch; Heinz Redl; Markus Huber-Lang (Clinical and Developmental Immunology)
Multiorgan failure (MOF) represents the leading cause of death in patients with sepsis and systemic inflammatory response syndrome (SIRS) following severe trauma. The underlying immune response is highly complex and involves activation of the complement system as a crucial entity of innate immunity. Uncontrolled activation of the complement system during sepsis and SIRS with in excessive generation of complement activation products contributes to an ensuing dysfunction of various organ systems. In the present review, mechanisms of the inflammatory response in the development of MOF in sepsis and SIRS with particular focus on the complement system are discussed.